PMODE I: Design and Development of an Observatory for Characterizing Giant Planet Atmospheres and Interiors - Shaw, Cody L.; Gulledge, Deborah J.; Swindle, Ryan; Jefferies, Stuart M.; Murphy, Neil (Frontiers in Astronomy and Space Sciences, 2022)
The giant planets of our Solar System are exotic laboratories, enshrouding keys which can be used to decipher planetary formation mysteries beneath their cloudy veils. Seismology provides a direct approach to probe beneath the visible cloud decks, and has long been considered a desirable and effective way to reveal the interior structure. To peer beneath the striking belts and zones of Jupiter and to complement previous measurements—both Doppler and gravimetric—we have designed and constructed a novel instrument suite. This set of instruments is called PMODE—the Planetary Multilevel Oscillations and Dynamics Experiment, and includes a Doppler imager to measure small shifts of the Jovian cloud decks; these velocimetric measurements contain information related to Jupiter’s internal global oscillations and atmospheric dynamics. We present a detailed description of this instrument suite, along with data reduction techniques and preliminary results (as instrumental validation) from a 24-day observational campaign using PMODE on the AEOS 3.6 m telescope atop Mount Haleakalā, Maui, HI during the summer of 2020, including a precise Doppler measurement of the Jovian zonal wind profile. Our dataset provides high sensitivity Doppler imaging measurements of Jupiter, and our independent detection of the well-studied zonal wind profile shows structural similarities to cloud-tracking measurements, demonstrating that our dataset may hold the potential to place future constraints on amplitudes and possible excitation mechanisms for the global modes of Jupiter.